Long-term care insurance, mental health of the elderly and its spillovers - Chen, Yunfei; Zhao, Hong (Frontiers in Public Health, 2023)
The paper studies the effects of the long-term care insurance (LTCI) program in China on the mental health of older adults and the well-being of their families. We employ the staggered difference-in-differences approach based on the LTCI pilots from 2015 to 2017. First, we find the LTCI program improves older adults’ happiness and reduces depression symptoms significantly. The effects on the improvement in memory and cognition are associated with the elderly with activities of daily living-related need for care. Second, the effects of LTCI are partially mediated through providing community services, relieving care burdens, and reducing the incidence of diseases. More importantly, LTCI coverage improves caregivers’ physical health and social activities, reflecting its welfare spillover effects. Furthermore, the relationship between LTCI and mental health differs due to the difference in LTCI designs and older adults’ demographic characteristics.